PENGARUH FOMO DAN BIAS EMOSIONAL TERHADAP NIAT INVESTASI SAHAM GENERASI Z PADA MAHASISWA AKUNTANSI UNTAD - Zaidan, Muhammad; Sugianto, Sugianto; Kahar, Abdul; Pakawaru, Muhammad Ilham (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
The rapid expansion of stock investment participation among Generation Z has drawn attention to the growing importance of behavioral factors in financial decision-making. Despite having formal knowledge in accounting and finance, young investors may still be influenced by psychological tendencies when forming investment intentions. This study investigates the effect of investment-related fear of missing out and emotional bias on stock investment intentions among undergraduate accounting students at Tadulako University. A quantitative research approach with an associative design was employed, utilizing data obtained from a self-administered questionnaire distributed to accounting students. The collected data were examined using multiple linear regression analysis. The findings reveal that investment-related fear of missing out and emotional bias contribute positively to students’ intentions to invest in stocks. These results indicate that investment intentions are not solely driven by rational financial considerations, but are also shaped by emotional and behavioral influences. The study underscores the need for financial education programs to incorporate behavioral awareness alongside technical knowledge in order to promote more informed and balanced investment decisions. As the research was conducted within a single institutional setting, future studies are encouraged to expand the scope of respondents and explore additional psychological or social determinants of investment behavior.